Scattering from Model Nonspherical Particles Theory and Applications to Environmental Physics - Borghese, Ferdinando; Denti, Paolo; Saija, Rosalba; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
The scattering of electromagnetic radiation by nonspherical particles has become an increasingly important research topic over the past 20 years. Instead of handling anisotropic particles of arbitrary shape, the authors consider the more amenable problem of aggregates of spherical particles. This is often a very satisfactory approach as the optical response of nonspherical particles depends more on their general symmetry and the quantity of refractive material than on the precise details of their shape. The book addresses a wide spectrum of applications, ranging from scattering properties of water droplets containing pollutants, atmospheric aerosols and ice crystals to the modeling of cosmic dust grains as aggregates. In this extended second edition the authors have encompassed all the new topics arising from their recent studies of cosmic dust grains. Thus many chapters were deeply revised and new chapters were added. The new material spans The description of the state of polarization of electromagnetic waves of general form The conservation theorems of combined systems of fields and particles The appropriate multipole expansion for waves of general wave vector and of general state of polarization A number of new applications The effects of radiation pressure and radiation torque on cosmic dust grains A study of the morphology of cosmic dust grains and of the distribution and polarization of the electromagnetic field in the interior of aggregated dust grains.
Multipole Fields -- Propagation Through an Assembly of Nonspherical Scatterers -- Radiation Force, Radiation Torque and Thermal Emission -- Multipole Expansions and Transition Matrix -- Transition Matrix of Single and Aggregated Spheres -- Scattering from Particles on a Plane Surface -- 7 Applications: Aggregated Spheres, Layered Spheres, and Spheres Containing Inclusions -- Applications: Single and Aggregated Spheres and Hemispheres on a Plane Interface -- Applications: Atmospheric Ice Crystals -- Applications: Cosmic Dust Grains.
Keywords: Physics; Earth sciences; Geophysics; Optics; Electrodynamics; Astrophysics; Space sciences; Physics; Optics and Electrodynamics; Earth Sciences, general; Geophysics/Geodesy.; Extraterrestrial Physics, Space Sciences; Astrophysics and Astroparticles; Electronic books